Macrophages and glial cells: Innate immune drivers of inflammatory arthritic pain perception from peripheral joints to the central nervous system - Malange, Kaue Franco; Navia-Pelaez, Juliana M.; Dias, Elayne Vieira; Lemes, Julia Borges Paes; Choi, Soo-Ho; Dos Santos, Gilson Goncalves; Yaksh, Tony L.; Corr, Maripat (Frontiers in Pain Research, 2022)
Millions of people suffer from arthritis worldwide, consistently struggling with daily activities due to debilitating pain evoked by this disease. Perhaps the most intensively investigated type of inflammatory arthritis is rheumatoid arthritis (RA), where, despite considerable advances in research and clinical management, gaps regarding the neuroimmune interactions that guide inflammation and chronic pain in this disease remain to be clarified. The pain and inflammation associated with arthritis are not isolated to the joints, and inflammatory mechanisms induced by different immune and glial cells in other tissues may affect the development of chronic pain that results from the disease. This review aims to provide an overview of the state-of-the-art research on the roles that innate immune, and glial cells play in the onset and maintenance of arthritis-associated pain, reviewing nociceptive pathways from the joint through the dorsal root ganglion, spinal circuits, and different structures in the brain. We will focus on the cellular mechanisms related to neuroinflammation and pain, and treatments targeting these mechanisms from the periphery and the CNS. A comprehensive understanding of the role these cells play in peripheral inflammation and initiation of pain and the central pathways in the spinal cord and brain will facilitate identifying new targets and pathways to aide in developing therapeutic strategies to treat joint pain associated with RA.